Systematic review of research barriers, facilitators, and stakeholders in long-term care and geriatric settings, and a conceptual mapping framework to build research capacity - Quoc Dinh Nguyen; Marie-France Forget; Xi Sophie Zhang; Catherine Richer; Renata Podbielski; Pierrette Gaudreau; Philippe Desmarais (BMC Geriatrics, 2023)
Abstract Background Older adults are underrepresented in research. Heterogeneity of research processes in this population, specifically in long-term care (LTC) and geriatric acute care (GAC), is not well described and may impede the design, planning, and conduct of research. In this study, we identified, quantified, and mapped stakeholders, research stages, and transversal themes of research processes, to develop a mapping framework to improve research capacity by better characterizing this heterogeneity. Methods Multicomponent mixed methods study. An environmental scan was used to initiate a preliminary framework. We conducted a systematic literature search on processes, barriers, and methods for clinical research in GAC and LTC to extract and update stakeholders, research stages, and themes. Importance and interactions of elements were synthesized via heatmaps by number of articles, mentions, and content intersections. Results For our initial framework and environmental scan, we surveyed 24 stakeholders. Of 9277 records, 68 articles were included in our systematic review and allowed us to identify 12 stakeholders, 13 research stages, 17 transversal themes (either barriers, facilitators, general themes, or recommendations), and 1868 intersections. Differences in relative importance between LTC and GAC emerged for stakeholders (staff, managers vs. caregivers, ethics committees), and for research stages (funding, facility recruitment vs. ethics, individual recruitment). Crucial themes according to specific stakeholders were collaboration for the research team; communication, trust, and human resources for managers; heterogeneity for patients and residents. A heatmap framework synthesizing vital stakeholders and themes per research stage was generated. Conclusions We identified and quantified the interactions between stakeholders, stages, and themes to characterize heterogeneity in LTC and GAC research. Our framework may serve as a blueprint to co-construct and improve each stage of the research process.